2017
DOI: 10.1080/10408436.2017.1370576
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments of Crystallographic Analysis Methods in the Scanning Electron Microscope for Applications in Metallurgy

Abstract: The field of metallurgy has greatly benefited from the development of electron microscopy over the last two decades. Scanning electron microscopy (SEM) has become a powerful tool for the investigation of nano-and microstructures. This article reviews the complete set of tools for crystallographic analysis in the SEM, i.e., electron backscatter diffraction (EBSD), transmission Kikuchi diffraction (TKD), and electron channeling contrast imaging (ECCI). We describe recent relevant developments in electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 144 publications
(184 reference statements)
0
25
0
Order By: Relevance
“…This contrast is known as electron channelling contrast and is closely related to diffraction contrast in a transmission electron microscope (TEM) (Zaefferer & Elhami, 2014;Borrajo-Pelaez & Hedströ m, 2018). The contrast obtained from detecting backscattered electrons in a scanning electron microscope (SEM) is dominated by the atomic number of the atoms in the probed volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrast is known as electron channelling contrast and is closely related to diffraction contrast in a transmission electron microscope (TEM) (Zaefferer & Elhami, 2014;Borrajo-Pelaez & Hedströ m, 2018). The contrast obtained from detecting backscattered electrons in a scanning electron microscope (SEM) is dominated by the atomic number of the atoms in the probed volume.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this contrast, the intensity of backscattered electrons originating from crystalline materials is affected by the lattice spacing and the orientation of the ISSN 1600-5767 # 2020 International Union of Crystallography crystal lattice with respect to the axis of the primary beam. This contrast is known as electron channelling contrast and is closely related to diffraction contrast in a transmission electron microscope (TEM) (Zaefferer & Elhami, 2014;Borrajo-Pelaez & Hedströ m, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Only three notable studies have been recently reported [40] [41] [42] but they are only qualitative and are limited by mere generalised phase identification. This is a new and unique technique which has been reported as complimentary to transmission electron microscopy [43] [44]. It has unique ability to identify [45] and map crystallinity in materials [46] [47] [48] [49].…”
Section: Introductionmentioning
confidence: 99%
“…With the help of energy dispersive X-ray spectroscopy (EDS) detector, it can also generate map of crystal structure of individual elements which can help identify their nature and microstructural features (e.g. primary, secondary and tertiary dendrite arm spacing) [43] [52]. It also generates pole figures and grain size histograms which again can be used to determine mechanical properties of material.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the quantification of the thickness using TEM, the main advantage of ECCI is its capability to capture a large amount of laths in a quicker way. It has proven to be a powerful tool when combined with EBSD to evaluate microstructural parameters like misorientation distribution [31]. EBSD analysis was specifically used here to evaluate the ''unit size'' and to perform correlative work with ECCI so as to identify precipitation at certain boundaries.…”
Section: Microstructure Evolution From Ecci and Ebsdmentioning
confidence: 99%